THE INFLUENCE OF MANAGER COMPETENCY ON KERINCI REGENCY GOVERNMENT ASSET PROCUREMENT PERFORMANCE - Sulistian, Reki; Yulius, M. Nursyaifi; Anif, Bahrul (Rang Teknik Journal, 2024)
This research has very important relevance because it investigates the impact of Human Resource Competencies, which include Knowledge, Skills and Attitudes, on asset procurement performance in the Kerinci Regency government landscape. Given the important role of resource management in public administration, this research aims to provide valuable insights for optimizing asset procurement strategies. Using a methodical approach, the research began with careful tabulation of data from 50 respondents representing various government departments. Statistical analysis, including KMO and Bartlett's tests, validates the correlation of competency factors, while the classical assumptions of the regression model ensure the robustness of the study. These findings show that there is a significant influence of Human Resource Competency on asset procurement results. Rigorous testing of validity, reliability, and classical assumptions increases the credibility of research results. The coefficient of determination shows a strong relationship between competency factors and procurement efficiency. In conclusion, this research contributes not only to the academic understanding of this subject but also offers practical implications for improving resource management strategies in public administration, thereby providing a foundation for future studies in this important domain.